The value of proteasome inhibition in cancer. Can the old drug, disulfiram, have a bright new future as a novel proteasome inhibitor? - Cvek, Boris; Dvorak, Zdenek (Drug discovery today, 2008)
The major approach to the development of anticancer drugs involves searching for new compounds, efficient against malignancies, which are not, as yet, used clinically. This strategy is time-consuming and expensive. Recent studies have disclosed a surprising, but mechanistically consistent, anticancer activity of disulfiram (antabuse), a drug used for about 50 years in the treatment of alcoholism. Disulfiram has been successfully used to suppress hepatic metastases originating from ocular melanoma. The pharmacokinetics of disulfiram and its pharmacological profile in cancer cell lines and in cancer cells obtained from patients is well known. Disulfiram is a readily available and inexpensive substance whose adverse effects are negligible, compared to classical cancerostatics. In addition, the inhibitory potency of disulfiram against the proteasome conforms to current anticancer strategies and represents a new, promising approach to proteasome inhibition.
Keywords: předpověď; Animals; Ubiquitin; inhibitory proteasomu; pyraziny; screeningové testy protinádorových léčiv; Neoplasms; nádory; Bortezomib; Pyrazines; Boronic Acids; lidé; Antineoplastic Agents; ubikvitin; protinádorové látky; odvykací prostředky alkoholu; Forecasting; thiokarbamáty; Proteasome Inhibitors; Disulfiram; proteasomový endopeptidasový komplex; Thiocarbamates; Alcohol Deterrents; disulfiram; Drug Screening Assays, Antitumor; bortezomib; NF-kappa B; zvířata; kyseliny boronové; Proteasome Endopeptidase Complex; Humans